TYPES AND IMPORTANCE OF MODERN EDUCATIONAL TECHNOLOGIES IN PHYSICS LESSONS ON THE PRIORITY OF INCLUSIVE EDUCATION - Urinova Kamala Komildjonovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article contains methodological recommendations for organizing physics classes for students with disabilities. Features of teaching children with disorders of the musculoskeletal system to solve physical problems are considered in detail.